2016
DOI: 10.3329/jom.v17i1.30054
|View full text |Cite
|
Sign up to set email alerts
|

Association of Hypertriglyceridemia with Ischemic Stroke, Study in a Tertiary Care Hospital in Bangladesh

Abstract: Abstract Abstract Abstract Backgr Backgr Backgr Backgr Background: ound: ound: ound: ound: Hypertriglyceridemia fosters the development of atherosclerosis via several mechanisms and lead to ischemic stroke (IS) through its contribution to thrombogenicity. The association of hypertriglyceridemia with ischemic stroke was evaluated in this study. Methods:Methods: Methods: Methods: Methods: This was a case control study conducted in the Department of Medicine, Dhaka Medical College Hospital and data was collected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…In terms of mode, the (Freiberg et al, 2009) among the general population in Denmark, high level of non-fasting triglycerides along with elevated LDL level are predictors of ischemic stroke. (Karim et al, 2016) in a study at Dhaka Medical College Hospital also confirmed the correlation between hypertriglycerides and the risk of ischemic stroke. There are several mechanisms that are thought to be contributing triglyceride pathways to the occurrence of ischemic stroke, among others through correlation with elevated levels C-reactive protein , its involvement in the process of atherosclerosis and thrombogenesis, as well as its ability to cause thrombogenic changes in the coagulation system and increase plasma viscosity (Antonios, Angiolillo and Silliman, 2008).…”
Section: Discussionmentioning
confidence: 61%
“…In terms of mode, the (Freiberg et al, 2009) among the general population in Denmark, high level of non-fasting triglycerides along with elevated LDL level are predictors of ischemic stroke. (Karim et al, 2016) in a study at Dhaka Medical College Hospital also confirmed the correlation between hypertriglycerides and the risk of ischemic stroke. There are several mechanisms that are thought to be contributing triglyceride pathways to the occurrence of ischemic stroke, among others through correlation with elevated levels C-reactive protein , its involvement in the process of atherosclerosis and thrombogenesis, as well as its ability to cause thrombogenic changes in the coagulation system and increase plasma viscosity (Antonios, Angiolillo and Silliman, 2008).…”
Section: Discussionmentioning
confidence: 61%
“…Other study also found that more than half of the subjects are having normal triglycerides. 16 According to AHA journal, triglycerides and total cholesterol level aren't independent risk for ischemic stroke, however there was a suggestion of increased risk for patients with high triglycerides and total cholesterol level. 17 High HDL in blood is considered good.…”
Section: Discussionmentioning
confidence: 99%